Definitions and Redefinitions of Urban Sustainability: A Bibliometric Approach - Hamman, Philippe (Environnement urbain)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2017)
This paper investigates evolutions in and alternatives to the “sustainable development” paradigm and examines these new trends. It offers a review of the social science literature that focuses on the language of the “sustainable city” used by researchers and experts in sociology, geography and urban studies since 2009. First, five main variants of “sustainable city” discourses are evidenced by the statistical and lexical analyses: the “recyclable city”, the “compact city”, the “green city”, the “just city” and the “participatory city”. They are often in conflict and subject to debate. Then, four main “alternatives” are identified: degrowth, resilience, sustainable transformation and transition. Yet they remain specific to restricted sectors or characterized by a binary vision.